Analisis Aspek Lingkungan dan Aspek Pemasaran Pada Usaha Quality Friend Chicken - Annisa; Ester; Erina; Yunita (Asosiasi Dosen Akuntansi Indonesia, 2023)
Quality Fried Chicken is a fast food restaurant that serves chicken products and other products related to chicken meat. The high growth of fast food restaurants in Indonesia will create competition among fast food restaurants in providing good products and services to consumers. Quality Fried Chicken must know aspects of its environment by maintaining cleanliness of good product and service quality if Quality Fried Chicken does not want its customers to move to other restaurants. To improve service quality, Quality Fried Chicken provides delivery service facilities to provide convenience to consumers who are reluctant to queue on location. The analysis technique used in this research is quantitative using interview and interview methods. This study also uses qualitative data analysis techniques, SWOT analysis techniques, and Potential Demand Projection Techniques (Trend Method).